Human Cytotoxic T Lymphocyte-Mediated Acute Liver Failure and Rescue by Immunoglobulin in Human Hepatocyte Transplant TK-NOG Mice - Uchida, Takuro (J Virol, 2015)
Hepatitis B virus (HBV)-specific cytotoxic T lymphocytes (CTLs) are critical in eliminating infection. We developed an animal model in which HBV-infected human hepatocytes are targeted by HBV-specific CTLs. After HBV inoculation in human hepatocyte-transplanted herpes simplex virus type-1 thymidine kinase-NOG mice, human peripheral blood mononuclear cells (PBMCs) were administered, and albumin, HBV DNA, alanine aminotransferase (ALT), and cytokine levels were analyzed. Histopathological and flow-cytometric analysis of infiltrating human immune cells were performed, and the efficacy of CTL-associated antigen-4 immunoglobulin (CTLA4Ig) against liver damage was evaluated. PBMC treatment resulted in massive hepatocyte damage with elevation of ALT, granzyme A, and gamma interferon and decrease in albumin and HBV DNA. The number of liver-infiltrating human lymphocytes and CD8-positive cells was significantly higher in HBV-infected mice. HBV-specific CTLs were detected by core and polymerase peptide-major histocompatibility complex-tetramer, and the population of regulatory T cells was significantly decreased in HBV-infected mice. Serum hepatitis B surface (HBs) antigen became negative, and HBs antibody appeared. CTLA4Ig treatment strongly inhibited infiltration of mononuclear cells. CTLA4Ig treatment will be used to treat patients who develop severe acute hepatitis B to prevent liver transplantation or lethality. This animal model is useful for virological and immunological analysis of HBV infection and to develop new therapies for severe acute hepatitis B. IMPORTANCE Without liver transplantation, some HBV-infected patients will die from severe liver damage due to acute overreaction of the immune system. No effective treatment exists, due in part to the lack of a suitable animal model. An animal model is necessary to investigate the mechanism of hepatitis and to develop therapeutic strategies to prevent acute liver failure in HBV infection. We developed an animal model in which HBV-infected human hepatocytes are targeted by human HBV-specific CTLs. In this model, HBV-infected human hepatocytes were transplanted into severely immunodeficient NOG mice in order to reconstruct elements of the human immune system. Using this model, we found that CTL-associated antigen-4 immunoglobulin was able to suppress damage to HBV-infected hepatocytes, suggesting an approach to treatment. This animal model is useful for virological and immunological analysis of HBV infection and to develop new therapies for severe acute hepatitis B.